CONCEPT LEARNING METHODS AND APPROACHES IN CONTEMPORARY LINGUISTICS WITH THE EXAMPLES OF “MOTHERLAND CONCEPT” - Javliyev Mansurbek Odil o’g’li (American Journals, 2024)
In the first quarter of the 20th century, a critical approach was taken to the comments about the concept. Only by the 80s, the need for this term reappears. Yu. S. Stepanov, in his research, tries to reveal the essence of mental formation and turns to the etymology of the word concept. Concept is a derivative of the Latin word conceptus. The concept has two aspects. On the one hand, culture enters the mental world of a person in the form of a concept, on the other hand, a person enters the culture with the help of a concept and sometimes influences it. While preserving his individual, unique culture, a person refers to the culture of peoples and the mental world of representatives of different nationalities through the concept.